KONSEP AT-TAISIR DALAM PERSPEKTIF HADIS - Darta, Ali (UIN Sumatera Utara Medan, 2020)
The teachings of Islam contained in the Qur'an and Hadith, in the implementation is not limited to one form of implementation only, but have some alternatives adapted to the condition of the person who will carry out, from which the basic legal haram can turn into a makruh even Mubah, or from whose legal basis is obligatory can be sunnah even jaiz. To reinforce the extent to which the Qur'an and Hadith discuss At-Taisir (lightening) in the teachings of Islam religion should be analyzed in the form of research with the title of At-Taisir (lightening) in the Qur'an and hadith. This type of research is qualitative with the method of library research (research Library), in general Metofe Yusuf Al-Qaradhawi is used to analyze Hadith and verses of the Qur'an and related to At-Taisir. But to deepen the meaning of the author's text use the abbreviation Ushul FIQH. After being examined there are several verses of the Koran and some saheeh hadith that speaks At-Taisir. Then from the verses and some of the hadith is concluded that the facility is valid due to several things: common sense, gender, human habit, human needs, compulsion, age and physical health. This article is expected to give an overview of the ease of carrying out Islamic religious teachings.